Advances in the study of artemisinin and its derivatives for the treatment of rheumatic skeletal disorders, autoimmune inflammatory diseases, and autoimmune disorders: a comprehensive review - Long, Zhiyong; Xiang, Wang; Xiao, Wei; Min, Yu; Qu, Fei; Zhang, Bolin; Zeng, Liuting (Frontiers in Immunology, 2024)
Artemisinin and its derivatives are widely recognized as first-line treatments for malaria worldwide. Recent studies have demonstrated that artemisinin-based antimalarial drugs, such as artesunate, dihydroartemisinin, and artemether, not only possess excellent antimalarial properties but also exhibit antitumor, antifungal, and immunomodulatory effects. Researchers globally have synthesized artemisinin derivatives like SM735, SM905, and SM934, which offer advantages such as low toxicity, high bioavailability, and potential immunosuppressive properties. These compounds induce immunosuppression by inhibiting the activation of pathogenic T cells, suppressing B cell activation and antibody production, and enhancing the differentiation of regulatory T cells. This review summarized the mechanisms by which artemisinin and its analogs modulate excessive inflammation and immune responses in rheumatic and skeletal diseases, autoimmune inflammatory diseases, and autoimmune disorders, through pathways including TNF, Toll-like receptors, IL-6, RANKL, MAPK, PI3K/AKT/mTOR, JAK/STAT, and NRF2/GPX4. Notably, in the context of the NF-κB pathway, artemisinin not only inhibits NF-κB expression by disrupting upstream cascades and/or directly binding to NF-κB but also downregulates multiple downstream genes controlled by NF-κB, including inflammatory chemokines and their receptors. These downstream targets regulate various immune cell functions, apoptosis, proliferation, signal transduction, and antioxidant responses, ultimately intervening in systemic autoimmune diseases and autoimmune responses in organs such as the kidneys, nervous system, skin, liver, and biliary system by modulating immune dysregulation and inflammatory responses. Ongoing multicenter randomized clinical trials are investigating the effects of these compounds on rheumatic, inflammatory, and autoimmune diseases, with the aim of translating promising preclinical data into clinical applications.